Fixed-dose combination of ivabradine and metoprolol in a patient with stable coronary artery disease: a case report - A. M. Shimkevich (Российский кардиологический журнал)
This article discusses a case of using fixed-dose combination of ivabradine/metoprolol in actual clinical practice.